An Extremely Rare Cause of Isolated Congenital Anosmia - Chia Saw; Noel David Friesen; Anthony Bartley (Case Reports in Otolaryngology)
A 14-year-old adolescent was referred to a regional paediatric outpatient clinic with anosmia by her family doctor in Western Australia. The patient has no recollection of her previous ability to smell, suggesting the possibility of congenital anosmia. She was assessed in the paediatric outpatient clinic. A “noncontrast high-resolution MRI-brain scan with Anosmia-Protocol” was requested as the first-line investigation of choice by the treating paediatrician. The MRI was reported as “absence of olfactory tracts with preserved olfactory bulb volume.” We report an extremely rare case of “isolated agenesis of the olfactory tract with intact olfactory bulbs” and discuss the clinical approach in bedside assessment of isolated congenital anosmia (ICA). Congenital anosmia can be a presentation of olfactory bulb aplasia; however, little is known about isolated olfactory tract agenesis and its treatment options. The patient was counselled on the diagnosis and safety advice provided.